2014
DOI: 10.1021/cn500242z
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Imaging Signatures Detect Amyloidopathy in Alzheimer’s Mouse Retina Well before Onset of Cognitive Decline

Abstract: Amyloidopathic disorders such as Alzheimer's disease present symptomology years after the entrenchment of amyloidogenic imbalance. The pathologic α-helix → β-strand conversion of amyloid β(1-42) and amyloid β(1-40) peptides causes neuronal death in the vicinity. Symptomology often presents only after significant neurodegeneration. This thus warrants early detection of amyloidopathy in Alzheimer's disease. Nonexistent modalities for direct identification and quantitation of soluble amyloid aggregates or (proto)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(127 citation statements)
references
References 38 publications
4
123
0
Order By: Relevance
“…In line with the above findings, numerous studies examining the retinas of sporadic and transgenic animal models of AD have reported Aβ deposits, vascular Aβ, pTau, and paired helical filament-tau (PHF-tau), often in association with RGC degeneration, local inflammation (i.e., microglial activation), and impairments of retinal structure and function (11,39,40,42,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61). These studies, which included a variety of transgenic rat and mouse models, as well as the sporadic rodent model of AD, Octodon degus, demonstrated abundant Aβ deposits, mainly in the innermost retinal layers (RGCs and NFL) (40,42,45,49,52,54,57).…”
Section: Introductionmentioning
confidence: 57%
“…In line with the above findings, numerous studies examining the retinas of sporadic and transgenic animal models of AD have reported Aβ deposits, vascular Aβ, pTau, and paired helical filament-tau (PHF-tau), often in association with RGC degeneration, local inflammation (i.e., microglial activation), and impairments of retinal structure and function (11,39,40,42,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61). These studies, which included a variety of transgenic rat and mouse models, as well as the sporadic rodent model of AD, Octodon degus, demonstrated abundant Aβ deposits, mainly in the innermost retinal layers (RGCs and NFL) (40,42,45,49,52,54,57).…”
Section: Introductionmentioning
confidence: 57%
“…These include the Tg2576, APP/PS1, 3xTg, 5xFAD mice, the TgF344-AD rat, and O. degus [1, 4648, 107, 117, 134, 148, 150, 152, 154, 178, 184]. It has been reported that levels of Aβ 40 and particularly Aβ 42 are elevated in the retina, as well as in the lens, vitreous humor, and choroid of AD rodent models (Table 2) [1, 46, 47, 117, 148, 150, 154, 178, 184].…”
Section: Ad-specific Ocular Pathology In Animal Modelsmentioning
confidence: 99%
“…Deposits of insoluble Aβ species and subsequent plaque formation have been documented in the retinas of Tg2576, APP SWE /PS1 ΔE9 , APP SWE /PS1 M146L/L286V , 3xTg, and 5xFAD mice, as well as O. degus [1, 4648, 107, 108, 117, 134, 139, 152, 184, 187, 188]. In the Tg2576 mouse, plaques have been identified most consistently in retinal layers ranging from the GCL to the ONL, and rarely in the photoreceptors and optic nerve [117, 184].…”
Section: Ad-specific Ocular Pathology In Animal Modelsmentioning
confidence: 99%
“…One such method is hyperspectral imaging, whereby tissue reflectance to a wide range of incident wavelengths are quantified (More and Vince, 2015). Using this technique, More and Vince (2015) were able to determine that Aβ has a unique hyperspectral signature, capable of distinguishing these deposits in ex vivo preparations of brain and retina from a mouse model of AD. More recently, the authors applied this technology to a live mouse retina, demonstrating that the hyperspectral signatures are preserved even when imaged through the ocular media.…”
Section: Retinal Biomarkersmentioning
confidence: 99%